(untitled) (Revista NUPEART, 2020)
This article is about questions: how and what to ask children in a pandemic situation, and about the questions-answers they gave to our questions. I describe, initially, the process of development shared between adults and children of a questionnaire aimed at children from 6 to 12 years who experienced the social isolation resulting from the Covid 19 pandemic. Next, I analyze some of the answers that were given format of questions. These questions emerge as a challenge, a doubt, a reflection of the children about the adult categories, demands and perceptions. The objective of this article is to problematize the child-adult relationship at the confluence of theater and anthropology research and to value the role of the question in this process.